High-frequency PCR-testing as a powerful approach for SARS-CoV-2 surveillance in the field of critical infrastructure: A longitudinal, retrospective study in a German tertiary care hospital - Bastian Fischer; Martin Farr; Jan Gummert; Cornelius Knabbe; Tanja Vollmer (PLoS ONE, 2025)
A high number of SARS-CoV-2 infections are mild, often even asymptomatic. Because of high specificity and sensitivity, RT-PCR is considered the gold-standard for COVID-19 testing. The technology played a key role in detecting sources of infection at an early stage and therefore preventing larger outbreaks. This was especially important in case of critical infrastructure, such as hospitals. Until now, comprehensive studies concerning the impact of high-frequency PCR-testing in German tertiary care hospitals during the COVID-19 pandemic are lacking. We therefore analyzed about 285.000 oral swab probes of 3.421 healthcare-workers concerning SARS-CoV-2 RNA positivity between November 2020 and February 2023. Our data show that frequent PCR-testing is a useful tool concerning SARS-CoV-2 surveillance. Due to the longitudinal character of the study, we were able to observe SARS-CoV-2 variant-specific differences. For example, the omicron-variant led to high reinfection-rates as well as lower Ct-values. Nevertheless, reinfection rates in our hospital are much lower compared to other analyzed healthcare-worker cohorts described in the literature, which is again attributable to the frequent testing-regime implemented in the early phase of the pandemic. Our data further reveal a longer infection-duration in elderly compared to younger individuals.